Impacts of climate change on hydrological droughts at basin scale: A case study of the Weihe River Basin, China. (20th April 2019) - Zhao, Panpan; Lü, Haishen; Yang, Huicai; Wang, Wenchuan; Fu, Guobin
Abstract: The likelihood changes of the numbers of occurrences, duration and intensity of hydrological droughts in the Weihe River Basin in China were investigated by using the bias-corrected future climate projections from three selected Global Climate Models (GCMs) with two emission scenarios (RCP 4.5, RCP 8.5), and Soil and Water Assessment Tool (SWAT) hydrological model. Results showed that: 1) The frequency of hydrological droughts, drought durations and intensities would have obvious increasing trends in the future under dry GCM condition. However, an opposite decreasing trend was shown under wet GCM condition; 2) Future precipitation changing direction and magnitudes were dominating factor for the likelihood changes of drought characteristics. Forty GCMs project a future precipitation change from −3.42% to +14.24%, which is the largest source of uncertainties. If the observed trends of precipitation and temperature during the last 50 years continue, then the Weihe River Basin would likely be in the dry condition of GCMs; 3) The impacts of temperature on hydrological droughts cannot be neglected and it has direct (evaporation and runoff generation) and larger magnitude indirect effects (precipitation patterns). The presented results have practical applications for regional drought mitigation planning under future climate changes.